Influence of Investment and Labour on Agriculture Sector Economy of South Kalimantan Province - Ahmad Yunani; Nasrudin Nasrudin (Journal of Wetlands Environmental Management, 2014)
The purpose of this study was to describe the development of investment and employment in South Kalimantan and to analyze the effect of investment and employment in the agricultural sector to GDP in South Kalimantan. This research is a quantitative study by conducting data collection at the Central Bureau of Statistics South Kalimantan Province pertaininglabour and the economy GDP Data and at Bappeda South Kalimantan and BKPMD (Investment Coordinating Board) South Kalimantan related PMA and PMD data investments as well as data from the Investment Credit Bank Indonesia Banjarmasin.The results showed that the province of South Kalimantan economy during the year 2002-2011grow positively. The condition is mainly supported by a number of industries (which are labour intensive) and the number of people working in agriculture, trade, and mining. However, no significant investment to GDP of Agriculture Sector in South Kalimantan was observed. Labour is still positive but not significant effect on GDP of Agriculture Sector. Taken together investment and employment significantly influence GDP of Agriculture Sector in South Kalimantan, though only 61.5% of the dependent variable explained by the independent variable, while the remaining 38.5% was explained by outside the regression model. It was suggested that the governments of South Kalimantan Province should do efforts to improve the quality of the labour force (i.e., by the local government. The role of the investment must also be adapted to the spirit of regional autonomy and should be encouraged to increase investment conducive situation, mapping the potential area and the establishment of integrated services in the unit for easy service creation and investment business license in order to avoid mistakes in investing and avoid systematic risks.